Development of a Yellow-Seeded Stable Allohexaploid Brassica Through Inter-Generic Somatic Hybridization With a High Degree of Fertility and Resistance to Sclerotinia sclerotiorum - Kumari, Preetesh; Singh, Kaushal Pratap; Kumar, Sundip; Yadava, Devendra Kumar (Frontiers in Plant Science, 2020)
The Brassica coenospecies have treasure troves of genes that could be beneficial if introgressed into cultivated Brassicas to combat the current conditions of climate change. Introducing genetic variability through plant speciation with polyploidization is well documented, where ploidy augmentation of intergeneric allohexaploids using somatic hybridization has significantly contributed to genetic base broadening. Sinapis alba is a wild member of the Brassicaceae family that possesses valuable genes, including genes conferring resistance to Sclerotinia sclerotiorum, Alternaria brassicae, pod shattering, heat, and drought stress. This work aimed to synthesize stable allohexaploid (AABBSS) Brassica, while incorporating the yellow-seed trait and resistance to S. sclerotiorum stem rot. The two fertile and stable allohexaploids were developed by polyethylene glycol mediated protoplast fusions between Brassica juncea (AABB) and S. alba (SS). These symmetric hybrids (2n=60) were validated using morphological and molecular cytology techniques and were found to be stable over consecutive generations. The complete chromosome constitution of the three genomes was determined through genomic in-situ hybridization of mitotic cells probed with S. alba genomic DNA labeled with fluorescein isothiocyanate. These two somatic hybrids showed 24 hybridization signals demonstrating the presence of complete diploid chromosomes from S. alba and 36 chromosomes from B. juncea. The meiotic pollen mother cell showed 30 bivalent sets of all the 60 chromosomes and none of univalent or trivalent observed during meiosis. Moreover, the backcross progeny 1 plants revealed 12 hybridization signals out of a total of 48 chromosome counts. Proper pairing and separation were recorded at the meiotic metaphase and anaphase, which proved the stability of the allohexaploid and their backcrossed progeny. When screening, the allohexaploid (JS2) of B. juncea and S. alba displayed a high degree of resistance to S. sclerotiorum rot along with a half-yellow and half-brown (mosaic) seed coat color, while the B. juncea and S. alba somatic hybrid1 (JS1) displayed a yellow seed coat color with the same degree of resistance to Sclerotinia rot.